Process analytical technology (PAT): applications to flow processes for active pharmaceutical ingredient (API) development. Issue 6 (31st March 2022) - Talicska, Courtney N.; O'Connell, Eamon C.; Ward, Howard W.; Diaz, Angel R.; Hardink, Mark A.; Foley, David A.; Connolly, Douglas; Girard, Kevin P.; Ljubicic, Tomislav
Abstract : Process analytical technology (PAT) applications pertaining to Pfizer's Flexible API Supply Technology (FAST) initiative. Abstract : As flow processes are being increasingly utilized for development of active pharmaceutical ingredients (APIs), the importance of process analytical technology (PAT) in the pharmaceutical industry is growing. Here, we describe a variety of PAT tools (FTIR, on-line UPLC-MS, flow NMR) used in support of flow chemistry platforms at Pfizer as part of the Flexible API Supply Technology (FAST) initiative. A blend of qualitative and quantitative PAT approaches are described, with each method tailored to the specific aims of each individual platform. PAT is demonstrated to be beneficial for real-time process understanding and for rapid optimization of chemical reactions in the flow-chemistry space, reducing the need for off-line analytics and helping to accelerate development timelines.